Double-Balloon Enteroscopy: Preliminary Experience in Patients with Obscure Gastrointestinal Bleeding or Chronic Abdominal Pain - May, A.; Nachbar, L.; Wardak, A.; Yamamoto, H.; Ell, C. (Endoscopy, 2003)
Background and Study Aims: Even in the era of capsule endoscopy, diseases of the small bowel are sometimes difficult to diagnose, and endoscopic treatment is not possible without surgical laparotomy. The new method of carrying out enteroscopy using a double-balloon technique allows not only diagnostic but also therapeutic endoscopic interventions for lesions in the small bowel. Preliminary experience with this new method is reported here. Patients and Methods: Between the end of March 2003 and August 2003, eight patients (four women, four men; mean age 59 ± 23 years, range 20 - 90) with chronic gastrointestinal bleeding or abdominal pain, or both, underwent enteroscopy using the double-balloon technique. Seven of the patients had been suffering from chronic gastrointestinal bleeding for 56 ± 49 months (range 3 - 120 months, median 48 months). The lowest hemoglobin levels ranged from 3.6 g/dl to 8.6 g/dl (mean 6.7 ± 1.7 g/dl), and a mean of 7.6 ± 5.6 (range 1 - 15) blood units had been transfused. Capsule endoscopy was carried out in six patients, revealing angiodysplasias in three, suspected Crohn’s disease in one, fresh blood in the small bowel without a lesion in one, and a focal enanthema in another patient. Results: Enteroscopy with the double-balloon technique was carried out using the oral approach in all patients and additionally with the anal approach in four patients. In two patients with multiple angiodysplasias, it was possible to examine the whole small bowel and to treat the angiodysplasias. All of the capsule endoscopy findings were confirmed; a definite bleeding source was found and treated in two patients with unclear bleeding, and in another patient the real bleeding source was found (not angiodysplasia). The enteroscopy system was easy to handle in all cases. No complications occurred. It was possible to carry out the procedure with the patients under sedoanalgesia. Conclusions: This new enteroscopy system is easy to handle and seems to be safe. Visualization of the whole small bowel is possible using both the oral and anal approaches. Enteroscopy with the double-balloon technique promises to become a standard method for diagnostic and therapeutic endoscopy of the small bowel without surgical laparotomy.